2014
DOI: 10.1111/bjd.13087
|View full text |Cite
|
Sign up to set email alerts
|

‘Happy’ drug survival of adalimumab, etanercept and ustekinumab in psoriasis in daily practice care: results from the BioCAPTUREnetwork

Abstract: Ustekinumab showed a better overall drug survival than etanercept, and a trend towards a better overall drug survival than adalimumab. After 1 year, patients reported to be 'happy' in 79% of episodes and 'unhappy' in 21%. We introduced the new concept of 'happy' drug survival because the proportion of on-drug patients with good quality of life is an important indicator for treatment success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
57
2
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 36 publications
20
57
2
13
Order By: Relevance
“…Table 3 summarizes all the studies published so far, where data were collected from large patient population of two or more centers, the follow-up period was at least one year, and the authors compared at least three or more biological therapies. The list includes five prospective registry-based studies and three retrospective studies (5,11,(16)(17)(18)(19)(20). Table 3 shows that those studies which included ustekinumab have found drug survival of ustekinumab superior to the drug survival of TNF-alpha inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 summarizes all the studies published so far, where data were collected from large patient population of two or more centers, the follow-up period was at least one year, and the authors compared at least three or more biological therapies. The list includes five prospective registry-based studies and three retrospective studies (5,11,(16)(17)(18)(19)(20). Table 3 shows that those studies which included ustekinumab have found drug survival of ustekinumab superior to the drug survival of TNF-alpha inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…A new concept of “happy drug survival” was introduced by combining quality of life measures with drug survival [73]. In a recent study based on BioCAPTURE registry data, the percentage of treatment episodes with “happy on-drug patients” increased from 27% at baseline to 79% after 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Bezüglich der Therapiepersistenz ("Drug survival") von Biologika bei Psoriasis ist die Datenlage teilweise uneinheitlich, und Langzeitdaten sind relativ rar [34][35][36][37] . Van den Reek et al fanden 1-Jahres-Persistenzraten von 85 % für Ustekinumab, 74 % für Adalimumab und 68 % für Etanercept [ 38 ] , Ergebnisse, die weitgehend mit Daten von Clemmensen et al übereinstimmen [ 39 ] . Eine andere Arbeitsgruppe do-Tabelle 3 Multivariate Regressionsmodelle zur Erfassung des Einflusses von soziodemografischen Charakteristika, Schwere und Dauer der Erkrankung, der Anzahl der systemischen Psoriasis-Therapien und der Therapiezufriedenheit auf die RIS von Prozesseigenschaften.…”
Section: Patienten Mit Einer Langen Krankheitsdauer Ein Besonderesunclassified
“…Levine und Kollegen identifi zierten Infl iximab als das Biologikum mit der größten Nachhaltigkeit und Ustekinumab als das Biologikum mit der geringsten Abbruchrate [ 41 ] . Erstens waren einige Studien monozentrisch [ 40,41 ] , während andere "Drug-survival"-Raten in großen landesweiten Kohorten untersuchten [34][35][36][37][38] . Die Unterschiede in den "Drug survival"-Raten können teilweise durch die Heterogenität der verschiedenen Studien erklärt werden.…”
Section: Patienten Mit Einer Langen Krankheitsdauer Ein Besonderesunclassified